Operational cost analysis of an Earth Station System using parallel configuration - W. Aris, Wan Muhammad Syaamil; Abdul Rahim, Nadirah (IEEE, 2023)
The earth station is crucial in delivering regular communication worldwide. Earth station requires costs to operate. The operational cost is the main cost involved in running the earth station. This operational cost can be split into maintenance, failure, and replacement costs. Moreover, the earth station also needs many complex subsystems, such as modulators and antennas to operate. These subsystems must also be maintained accordingly, or they will not work as intended. There are a lot of maintenance strategies that are readily available for the organization to be used. These strategies will indirectly affect both the failure and the replacement costs. Currently, three replacement methods are available: failure-triggered replacement, the age-based replacement method, and a hybrid version of the previous two methods. As for the cost estimation method, Activity-Based Costing (ABC) is used in this research. Monte Carlo from MATLAB software is utilized to simulate the selected replacement methods and the most efficient method to replace the earth system subsystems is selected. The contribution of the research is achieved through obtaining the smallest operational cost value. The results demonstrate that the failure triggered replacement method is way cheaper than the age-based replacement method with a value of $200.8947e10 and $224.1175e10 respectively.